Treadmill exercise has healing effects on obesity-induced sexual behavior disorder through kisspeptin and kiss1R expression in male rats - Kacar, Emine; Bulmus, Ozgur; Ercan, Zubeyde; Kavuran, Ilay Buran; Zorlu, Gokhan; Tan, Fatih; Kelestimur, Haluk (C M B Assoc, 2023)
The basic objective of this study was to examine the possible effects of treadmill exercise on obesity-related sexual behavior disorder in obese male rats and the role of kisspeptin in this effect. The rats were separated from their mothers at the age of 3 weeks, and classified into four groups as Control (C): normal diet-sedentary group, Exercise (E): normal diet-exercise group, Obese (O): high-fat diet-sedentary group, Obese + Exercise (O+E): high-fat diet-exercise grouSexual behavioral testing was conducted in the rats. At the end of the study, brain samples were taken from the animals for gene expression analyses. The treadmill exercise caused a significant increase in the O+E Group compared to the O Group in kisspeptin and kiss1R gene expression and in EF, ML, IL, MF, IF, III, EL, PEI, IR1, MFT, IFT, IRT sexual behavior parameters (p<0.05), and a significant decrease in ML, IL, III, EL sexual behavior parameters (p<0.05). Treadmill exercise caused a significant decrease in EF, ML, IL, MF, IF, III, EL, PEI, IR1, MFT, IFT, IRT sexual behavior parameters and kisspeptin and kiss1R gene expression in the hypothalamus, hippocampus, prefrontal cortex and corpus striatum in E Group compared to C Group (p<0.05), and a significant increase in ML, IL, III, EL sexual behavior parameters (p<0.05). Based on this effect, we believe that it is caused by an increase in kisspeptin and kiss1R expression in the hypothalamus, hippocampus, prefrontal cortex and corpus striatum. In conclusion, treadmill exerciseinduced kisspeptin secretion may increase GnRH secretion and cause hypothalamo-pituitary gonadal axis activation and ameliorative effect on deteriorated sexual function.
Keywords: Obesity; sexual behavior; tread-mill exercise; Kiss1; Kiss1R